Planning Analysis on Bridge Construction Possibilities and Challenges: A Review - Cayitho Calveen; Andri Irfan Rifai (Fakultas Teknik Sipil dan Perencanaan, 2023)
In every construction project, there will be many challenges and problems that will be passed. Therefore, this research is conducted to see some of the issues that were experienced by previous projects so that mistakes do not occur and can prevent failures or delays in the construction of bridges which are a group of a large project and cannot be considered trivial and requires detailed research and analysis during the construction process as well as its design. Bridges are very complicated infrastructures. In many cases, bridge structures are subjected to high traffic volumes and high loads. Procedures to ensure safe, successful, and secure systems are therefore vital. The paper presents various possibilities in choosing idea bridges, structures, and management; project management is an important factor supporting the project's success by analyzing the project management so that objectivity can be achieved most efficiently. The data collection method was carried out by a literature review from some journals. The starting point for problems in bridge construction has many impacts that affect both the design and construction periods as well as the maintenance period and the usage period of the bridge can also have an effect on the age of the bridge and can be caused by the environment, the materials used can also have an impact on the quality of the bridge and its lifespan, and if it is not planned properly it can have negative impacts such as economic, environmental impacts and the most critical is the loss of life.